Government effects on the distribution of income: an overview - Dimitri B. Papadimitriou (Levy Economics Institute of Bard College, 2006)
This paper is the overview chapter of an edited volume on The Distributional Effects of Government Spending and Taxation. The paper offers the author's perspective on the government's role as a redistributive agent. Taxation and public spending programs are analyzed using the experiences of the United States and other OECD countries. The stark differences among the respective welfare systems are examined from an economic policy lens assessing the success and failure of the tested social policy programs. The measurement and distribution of well-being for special segments of the population, i.e., the elderly and women, are considered.
Keywords: 330